THEORETICAL ICAL ASSUMPTIONS AND THEORETICAL BACK SAND THEORETICAL BACKING FOR SOCIAL SCIENCE RESEARCH: THEORETICAL ANALYSIS - Bakar, Ass. Prof. Mustafa (Dirasat in Economics and Business, 2004)
The design of a research project starts with the choice of a topic and a paradigm (Creswell, 1994). Further, methods , methodology and theory of any research project should be all defined (Ryan et al., 2002, p.8; Summerfield and Eye, 2003; and Dale, 2004) The purpose of this article is to explain the assumptions underlying the paradigms suggested by Burrell and Morgan (1979), discusse the criteria for selecting a paradigm in general and to show that researchers' own values, theoretical assumptions , theoretical backing and research methods should be all related to each other and to the aim of the research and clearly defined.